AN EXAMINATION OF MULTIDIMENSIONAL POVERTY PROFILE IN LIMPOPO, SOUTH AFRICA: IMPLICATION FOR USING CBMS GENERATED DATA IN LOCALISING SUSTAINABLE DEVELOPMENT GOALS, 2030 (Proceedings of the International Conference on Poverty and Sustainable Development, 2018)
This study sought to profile multidimensional poverty in Tzaneen Local Municipality in Limpopo province in South Africa. The objective was to profile multidimensional poverty and further demonstrate the implication of Community-Based system (CBMS) generated data in localizing Sustainable Development goals 2030 at the municipality level. Consultative and CBMS design approach was adopted in the study. Administered household questionnaire was used to census 1,534households in Tzaneen Local Municipality Ward1. Indicators for poverty measurements were generated in partnership with local municipality and aligned to relevant sustainable development goals 2030. Data was captured using Excel software and imported to CSPro6.3 software for analysis. Community-Based Monitoring-National Research Database (CBMS-NRDB) software was used to generate poverty maps. Community validation approach was used to authenticate the study findings. We conclude that CBMS can generate multidimensional poverty profile and maps which can be used to localize Sustainable Development goals at municipality levels. We recommend that the local municipality use CBMS generated data to profile multidimensional poverty and as a baseline for localizing Sustainable Development goals 2030.
Keywords: Poverty; Sustainable development goals; community-based; South Africa